Internet Sources - Information Culture in The Development of Student Communication Powers - Makhmudova Dilshoda Kurbonbayevna (Genius Journals, 2021)
This article discusses the current stage of development of society, the improvement of technology, information culture in the development of students' communication skills and their effective use.
Keywords: Technological processes; globalization; foreign Internet resources; integral